The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.12957/psi.saber.soc.2015.14840
|View full text |Cite
|
Sign up to set email alerts
|

Concepções da masculinidade: suas associações com os valores e a honra

Abstract: RESUMO:Este trabalho objetivou investigar a relação entre concepções de masculinidade, a preocupação com a honra e os valores humanos entre homens e mulheres. ABSTRACT: This research aimed at investigating the relationship among conceptions of masculinity, honor concerns and human values for men and women. To test these associations, two studies were conducted. In Study 1, participants were 275 people from general population with ages ranging from 17 to 49 years (M = 22.00, SD = 5.03), consisting mostly of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
1
7
0
10
Order By: Relevance
“…While men tend to avoid emotions, which would be a sign of weakness, women tend to welcome them. Guerra, Scarpati, Brasil, Livramento, and Silva (2015) corroborated the present authors, demonstrating that the emotional restriction for men is associated with personal stability and survival in groups that they are part of because the expression of emotions can be understood as a threat to masculinity. In addition, surveys have shown that women tend to experience more intense emotional loneliness than men (JongGierveld & Tilburg, 2010;Pinquart and Sorensen, 2001), a type of loneliness that showed a signifi cant positive correlation and average magnitude with regard to the fear of loneliness in the second study, which may help explain the greater fear presented.…”
Section: Discussionsupporting
confidence: 90%
“…While men tend to avoid emotions, which would be a sign of weakness, women tend to welcome them. Guerra, Scarpati, Brasil, Livramento, and Silva (2015) corroborated the present authors, demonstrating that the emotional restriction for men is associated with personal stability and survival in groups that they are part of because the expression of emotions can be understood as a threat to masculinity. In addition, surveys have shown that women tend to experience more intense emotional loneliness than men (JongGierveld & Tilburg, 2010;Pinquart and Sorensen, 2001), a type of loneliness that showed a signifi cant positive correlation and average magnitude with regard to the fear of loneliness in the second study, which may help explain the greater fear presented.…”
Section: Discussionsupporting
confidence: 90%
“…The 13 research participants were aged between 27 and 54 years old, and most of them declared themselves to be black (11), religious (12), having higher education (6), and a family income of two to ten minimum wages (8).…”
Section: Resultsmentioning
confidence: 99%
“…Another socially valued element is male honor, which is related to the dignity, esteem, and consideration of others, being associated with the social position occupied by men and based on situations considered to be positive, such as paying their debts and keeping promises (8) . Despite being considered a virtue, this masculine attribute, until the late 1970s, was commonly used to justify the practice of violence against women, including femicides, by their husbands, ex-husbands, and partners (9) , under the argument of "legitimate defense of honor. "…”
Section: Introductionmentioning
confidence: 99%
“…Concretamente, como indicam Maio e Esses (2001), homens podem aprender a evitar emoções, pois expressá-las seria algo incongruente com as concepções de masculinidade, sendo considerado um sinal de fraqueza (Guerra, Scarpati, Brasil, Livramento, & Silva, 2015). Por outro lado, a figura tradicional das mulheres como cuidadoras pode levá-las a se aproximarem de emoções, permitindo-lhes a identificação com as experiências emocionais dos outros.…”
Section: Discussionunclassified